Pemberian Penghargaan Untuk Meningkatkan Kualitas Guru di Madrasah Ibtidaiyah: Tinjauan Strategi Kepala Sekolah - Husnunnadia, Ratu; Masyithoh, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research discusses the impact of awards given by school principals to teachers at Madrasah Ibtidaiyah on teacher quality which includes motivation and performance. The literature review method was used by analyzing ten articles related to awards in improving teacher quality. The results of the analysis show that rewards given by school principals, such as praise, bonuses, certificates, or professional development opportunities, have a positive impact on teacher work motivation. This award also influences the improvement of teacher performance in teaching and guiding students. School principals have an important role in motivating teachers through rewards, which can create a more effective and quality educational environment. Therefore, bold and innovative reward strategies need to be developed and implemented to improve the overall quality of education. Thus, this research provides insight into the importance of rewards for teachers and contributes to developing new strategies to strengthen the quality of teacher teaching.